Spin transport and magnetic correlation parameters for graphene-like nanocarbon sheets doped with nitrogen - Alegaonkar, Ashwini P.; Kumar, Arvind; Patil, Sagar H.; Patil, Kashinath R.; Pardeshi, Satish K.; Alegaonkar, Prashant S. (Journal of Physical Chemistry C, 2013)
Globally, graphene magnetism has captivated the attention of researchers in recent years. To obtain magnetic ordering, irregularities in the carbon network, like defects, adatoms, etc., are essential. Herein, we report on spin transport and magnetic correlations in graphene-like nanocarbon sheets (GNCs) that were doped with nitrogen by use of tetrakis(dimethylamino)ethylene (TDAE). The spin transport measurements, performed by electron spin resonance technique, showed that both spin-spin and spin-lattice relaxation times are increased by nitrogen doping. The magnetic correlations, measured on a vibrating sample magnetometer, showed that ordering parameters are reduced for nitrogen-loaded GNCs. Chemical analysis, carried out via electron spectroscopy, revealed that nitrogen atoms exchange couples electron-to-hole with the carbon network Analysis of I-V measurements showed that higher-order resistance is appreciably decreased for nitrogen-doped GNCs. The observed decrease is due to an increase in nonbonding states baying small local density. After doping, states in this region may be localized pi spin populated around the doped region. By and large, the approximately 20% magnetization that exists in GNCs is found to be reduced to 5% by introduction of nitrogen.